(untitled) (Educational Dimension, 2021)
The Educational Technology Quarterly (ETQ) is a new Diamond Open Access peer-reviewed journal by the Academy of Cognitive and Natural Sciences. The journal focuses on the ways in which digital technology can enhance education and welcomes research papers on the pedagogical uses of digital technology where the focus is broad enough to be of interest to a wider education community. In addition to empirical work, ETQ also welcomes systematic reviews and meta-analyses that include clear research questions, a framework of analysis, and conclusions that reflect the aims of the paper. The journal is published four times a year in March, June, September, and December. The first issue of ETQ was published in March 2021.